Effect of Emotional Intelligence on Employee Engagement and Job Satisfaction with Work-Life Balance as Intervening Variables in the Generation Z in Surabaya - Nurjanah, Diyang; Indawati, Nurul (CV ODIS, 2021)
The purpose of this research is to determine the influence of emotional intelligence, employee engagement, and job satisfaction with work-life balance as a mediating variable. This study focuses on Generation z who live in Surabaya, which based on BPS data, the city of Surabaya has the largest population in East Java and is dominated by Generation z. This research uses an online questionnaire to get the respondent, uses 100 samples respondents of Generation z in Surabaya city. Analysis with SmartPLS 3.3 analysis tools. This research found that emotional intelligence statistically significant positive to employee engagement, emotional intelligence does not affect job satisfaction. This research also proves that work-life balance successfully mediate the influence of emotional intelligence and employee engagement and successfully perfect mediate between emotional intelligence on job satisfaction, so emotional intelligence can affect job satisfaction through work-life balance.